Associative and sensorimotor learning for parenting involves mirror neurons under the influence of oxytocin. (29th April 2014) - Ho, S. Shaun; MacDonald, Adam; Swain, James E.
Abstract: Mirror neuron–based associative learning may be understood according to associative learning theories, in addition to sensorimotor learning theories. This is important for a comprehensive understanding of the role of mirror neurons and related hormone modulators, such as oxytocin, in complex social interactions such as among parent–infant dyads and in examples of mirror neuron function that involve abnormal motor systems such as depression.